La gramática castellana de Caramuel (1663) - Martínez Gavilán, María Dolores (1990)
Juan Caramuel y Lobkowitz (born Madrid, 1606-died Vigevano, 1682) was the author of a philosophical mediaeval style grammar in which many of the postulares of the speculative grammar Grammatica audax (1654) are resucitated. This must connected with his position in the terrain of philosophy and theology wich was clearly a scolastic one. Indeed, he has been considered as one of the forerunnes of the Grammaire générale et raisonnée of Port-Royal His contributions to the field of general or universal grammar ha ve been put finto relief by various scholars (V. Salmon, H E. Brekle, G. A. Padley, E Delgado) whose points of view are reviewed here.The objetive of what follows is two-fold a) to analyze his contribution to the fíeld of specific grammar, with especial reference to Spanish grammar, and b) to disco ver to what extent the anlytic guidelines employed in his general grammar are present there.We will be dealing with the brief Castillian grammar which is included in his poetic treatise Primos Calamos (Rome, 1663). In this study a symbiosis of the topics developed by classic Greek-latin and later assimilated by the grammars of common or vulgar languages can be observed, together with some of the beginnings of the speculative mediaeval grammar, which the author had applied previously in his philosophic grammar.
Juan Caramuel y Lobkowitz (Madrid, 1606-Vigevano, 1682), autor de una gramática filosófica de corte medieval en la que se resucitan muchos de los postulados de la gramática especulativa, Grammatica audax (1654) -hecho que se debe conectar con su posición claramente escolástica en el terreno de la filosofía y de la teología-, ha sido considerado uno de los antecedentes de la Grammaire généle et raisonnée de Port-Royal. Sus aportaciones en el terreno de la gramática general o universal han sido puestas de relieve por varios estudiosos (V. Salmon, H.E. Brekle, G. A. Padley, F. Delgado), cuyos puntos de vista se recogen aquí.Pero el objetivo de estas páginas es analizar su contribución en el campo de la gramática particular, y, en concreto, de la gramática española, y comprobar en qué medida están ahí presentes las pautas de análisis empleadas en su gramática general. Para ello nos basamos en la breve gramática castellana incluida en su tratado de poética Primos Calamos (Roma, 1663), obra en la que se observa una simbiosis de los planteamientos desarrollados por la gramática grecolatina clásica, asimilados por las gramáticas de las lenguas vulgares, y de algunos de los principios de la gramática especulativa medieval, que el autor había aplicado previamente en su gramática filosófica.
Keywords: Caramuel Lobkowitz, Juan, -- 1606-1682 -- 1663; Gramática; Lengua española